THE IMPACT OF HALAL PRODUCT KNOWLEDGE ON PURCHASE INTENTION BY ENHANCING ATTITUDES TOWARD HALAL FOOD - Lazuardy, Ilman Taufiq; Hidayat, Anas (Jurnal Ekonomi dan Bisnis, 2025)
This research aims to analyze the role of halal product knowledge on halal food purchase intention through increasing attitudes towards halal food. Using quantitative methods with a survey approach, data was collected from 400 Muslim respondents in Yogyakarta who were aware of the importance of halal food. The research results show that knowledge of halal products significantly influences attitudes towards halal food, which ultimately increases the intention to purchase halal food. The implications of this research support the importance of halal education for consumers to strengthen the halal food market.